Buya Yahya's View of Religious Moderation: Study of Youtube Content in Al-Bahjah TV Channel - Niken Setia Putri; Anindyah Dwi Septiyani; Avrin Lailatul Magfiroh; Lulu Aulia Putri; Sulistiyo Ningsih; Durrotul Mustafidah (TATHO: International Journal of Islamic Thought and Sciences, 2024)
The purpose of this study is to clarify the signs of understanding religious moderation in Indonesia in Buya Yahya's view on the You Tube channel (Al-Bahjah TV). The observation technique of You Tube content material is used in collecting research data. Meanwhile, data analysis through content analysis. The results of the study state that in Buya Yahya's view, the promotion of religious moderation is a positive thing for the lives of Muslims in Indonesia as long as it does not conflict with Islamic values, both in value and practice. This is because in Buya Yahya's view, Islam actually contains wasatiyah teachings that require Muslims to be neither extreme left nor right. This research confirms that religious moderation in Indonesia can be synergistic with the spirit of the teachings of the formation of moderate Islamic religiosity as long as the value content and practice of its practice can be synergistic. The limitations of this research do not identify the constraints on the understanding of viewers who understand Buya Yahya's views related to religious moderation in Al-Bahjah TV.